Adab Membaca Al-QurÄn - Musthofa musthofa (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
Reading the Holly Qur'an is a worthy practice of worshiping God, which can be done by empowering oral, eye (sight), hearing, mind and heart. Reading the Holly QurÄn is the command of Allah and His Messenger, so it takes knowledge of the ordinance to read it in order to avoid mistakes. Therefore, reading the Holly Qur'an well and correctly is required adabs to perform it. They are adab before, when, and after reciting the Holly QurÄn. Adab before reading Holly Al-QurÄn to be fulfilled include the intention of worship, holy of small and large hadas, facing qiblat, covering the private parts, clean and holy clothes, and place unclean (holy), and reading ta'awuz. Adab when reading the Holly Qur'an includes reading with tartiles, beautifying readings, loud voices, remembering the content of reading, living it out, and crying when reading it. Adab after reciting the Holly Qur'an is commanded to practice the content of Holly Al-QurÄn content, to love and follow Allah and His Messenger, and to take instruction.